The Trp53-Trp53inp1-Tnfrsf10b Pathway Regulates the Radiation Response of Mouse Spermatogonial Stem Cells - Kei Ishii (Stem Cell Reports, 2014)
Germ cells are thought to exhibit a unique DNA damage response that differs from that of somatic stem cells, and previous studies suggested that Trp53 is not involved in the survival of spermatogonial stem cells (SSCs) after irradiation. Here, we report a critical role for the Trp53-Trp53inp1-Tnfrsf10b pathway during radiation-induced SSC apoptosis. Spermatogonial transplantation revealed that Trp53 deficiency increased the survival of SSCs after irradiation. Although Bbc3, a member of the intrinsic apoptotic pathway, was implicated in apoptosis of germ and somatic stem cells, Bbc3 depletion inhibited apoptosis in committed spermatogonia, but not in SSCs. In contrast, inhibition of Tnfrsf10b, an extrinsic apoptosis regulator, rescued SSCs. Tnfrsf10b, whose deficiency protected SSCs, was upregulated by Trp53inp1 upon irradiation. These results suggest that the Trp53-Trp53inp1-Tnfrsf10b pathway responds to genotoxic damage in SSCs and that stem and progenitor cells exhibit distinct DNA damage responses in self-renewing tissue.